On Teaching of Discrete Mathematics - Yessenbayeva, G.A.; Ulbrikht, О.I. (Publ.KarSU, 2016)
This article is designed to help teachers make discrete mathematics more meaningful and understandable for the students. Teachers all over the world have developed different ways to teach discrete mathematics suc- cessfully in order to raise standards of achievement. This article brings together some of these tried and tested ideas from teachers, including the extensive experience of mathematical teachers and their colleagues working together in higher schools. The article is aimed at improvement of quality of teaching of discrete mathematics. In addition to understanding some issues that the teachers face in a mathematics classroom, we have included some teaching strategies of teaching mathematics. Мақала оқытушыларға көмек ретінде дискреттік математиканы студенттерге аса мағыналы жəне түсінікті жеткізу үшін арналған. Жетістіктер деңгейін арттыру мақсатында бүкіл əлем оқытушылары дискреттік математиканы оқытудың түрлі тəсілдерін ойлап тапты. Бұл мақалада оқытушылардың, сондай-ақ жоғарғы оқу орындарында жұмыс істейтін коп тəжірибелі математика пəнінің оқытушылары мен олардың əріптестерінің кейбір тексерілген жəне зерттелген пікірлері жиналған. Авторлар дискреттік математиканы оқытуда сапа деңгейін арттыруға атсалысқан. Сонымен қатар математикалық сыныптарда кездесетін кейбір сұрақтарды түсінуге қосымша ретінде математиканы оқытудың кейбір оқыту стратегияларын енгізген. Цель статьи — улучшить качество преподавания дискретной математики, сделать ее более осмысленной и понятной для студентов. Авторами проанализирован обширный опыт работы преподавателей математики высших учебных заведений и общеобразовательных школ. Рассмотрены различные способы обучения дискретной математике в целях повышения уровня учебных достижений. Разработаны некоторые обучающие стратегии преподавания математики по отдельным вопросам, с которыми сталкиваются преподаватели в математических классах.
Дискреттік математиканы оқыту туралы
О преподавании дискретной математики
Keywords: discrete mathematics; set theory; combinatorics; graph theory; genetic approach to the teaching of discrete mathematics; Petri nets